2020
DOI: 10.1055/s-0040-1710369
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Resurfacing Does Not Improve Clinical Outcome in Patients with Symptomatic Tricompartmental Knee Osteoarthritis. An RCT Study of 40 Patients Receiving Primary Cruciate Retaining Total Knee Arthroplasty

Abstract: There is some evidence that patellofemoral (PF) joint osteoarthritis (OA) causes anterior knee pain (AKP) after total knee arthroplasty (TKA). We hypothesized that patellar resurfacing in primary TKA for patients with symptomatic tricompartmental knee OA yields better clinical results after 2 years than non-resurfacing. A single center randomized controlled clinical trial comparing 40 patients receiving 42 cruciate retaining TKAs with (n = 21) or without patellar resurfacing (n = 21) was conducted. Primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…The mean follow-up periods in the trials ranged from 0.5 to 10 years with a weighted mean of 6.3 years. Using the Cochrane Risk of Bias tool, 11 trials demonstrated a low risk of bias in all domains [ 30 , 34 , 39 , 42 , 48 , 51 – 54 , 57 , 58 ]. Five trials demonstrated a high risk of bias in one or more domains [ 1 , 31 , 38 , 40 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean follow-up periods in the trials ranged from 0.5 to 10 years with a weighted mean of 6.3 years. Using the Cochrane Risk of Bias tool, 11 trials demonstrated a low risk of bias in all domains [ 30 , 34 , 39 , 42 , 48 , 51 – 54 , 57 , 58 ]. Five trials demonstrated a high risk of bias in one or more domains [ 1 , 31 , 38 , 40 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the risk of reoperation (15 studies) [ 1 , 29 , 35 , 37 39 , 44 46 , 50 , 53 , 55 – 58 ] comparing patellar resurfacing vs. no resurfacing: RR (CIs) = 0.70 (0.44–1.13; I 2 = 0%; CI = 0–54%; p for heterogeneity = 0.87); however patellar resurfacing reduced the risk of revision (17 studies) [ 19 , 31 , 33 , 39 , 40 , 42 , 44 , 47 , 51 – 58 ]: RR (CIs) = 0.63 (0.42–0.94; I 2 = 0%; CI = 0–51%; p for heterogeneity = 0.95) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the registry does not include clinical symptoms like anterior knee pain, patellar osteoarthritis, or other specific details of the patella. The presence of osteoarthritis of the patella may influence the decision to perform primary patellar resurfacing, although some authors find that this presence does not influence the outcome of the resurfacing ( 8 , 29 ). Third, the registry registers the rate only of patellar resurfacing of hospitals, not of individual surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature remains controversial as it provides no conclusive evidence in support of a patellar resurfacing vs. non-resurfacing regime ( 5 , 8 , 9 ). A meta-analysis showed that the number of revision surgeries was lower following TKA with patellar resurfacing than without ( 10 ).…”
mentioning
confidence: 99%
“…Moreover, there is a lack of evidence that patellar cartilage loss identified during TKA causes anterior knee pain or decreased function [ 6 ]. Some studies have reported that there were no differences in outcomes between patients who underwent or did not undergo patellar resurfacing, regardless of the degree of patellar cartilage loss [ 7 9 ]. The authors of one study reported satisfactory radiologic outcomes with patellar retention in patients with grade 4 advanced osteoarthritis (OA) in the patellofemoral joint [ 10 ].…”
Section: Introductionmentioning
confidence: 99%